Long interspersed nuclear element (LINE)-1 methylation level as a molecular marker of early gastric cancer. Issue 9 (September 2016) - Kim, Eun Jung; Chung, Woo Chul; Kim, Dae Bum; Kim, Yeon-Ji; Lee, Ji Min; Jung, Ji Han; Lee, Yun Kyung
Abstract: Background/aims: This study was performed to examine the state of long interspersed nuclear element (LINE)-1 methylation level in gastric epithelial dysplasias (GEDs) and evaluate as a molecular marker for gastric carcinogenesis when it was compared with RUNX3 expression. Methods: We examined 89 patients with GEDs subcategorized by the Vienna classification – 41 category 3 (low grade) and 48 category 4 (high grade/intramucosal carcinoma) lesion. All tissue samples were evaluated for RUNX3 immunohistochemical staining and the level of LINE-1 methylation. Results: The rate of negative expression of RUNX3 in category 4 lesion was significant higher than category 3 ( P  < 0.01). LINE-1 methylation level was statistically different between category 3 and category 4 lesion ( P  < 0.01). Between positive and negative expression of RUNX3 in GEDs, there was a significant difference of LINE-1 methylation level ( P  < 0.01). The area under the ROC curve (AUC) of LINE-1 methylation level for diagnosis of category 4 lesion was 0.88 (95% CI, 0.76–1.00). Conclusions: LINE-1 methylation level was well correlated with the Vienna classification of GED and it had a close relationship with the negative expression of RUNX3 in category 4 lesion. LINE-1 methylation level could be a good candidate for a molecular marker of early gastric cancer.